(3GdeNJUQ HGdBjGJ GdHjfGJ aj hdGOI HYV GdCehGJs
(3ChdgG (B:s
(3hHYO adeG Jhai TjNfG GdTjN eMeO aGVd QVj Gddg Yfg hCQVGg hCcQe ai OGQGdfYje eKhGfG s
(3BNQgG (B:s
(3hbO bGd JYGdi(B:" (3GdNHjKGJ ddNHjKjf hGdNHjKhf ddNHjKGJ hGdWjHGJ ddWjHjf hGdWjHhf ddWjHGJ(B" (3hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(593) s
Keywords: (3GdJhMjO hGdedd hGdfMds